Restrição nutricional em mudas de teca e seu efeito na preferência de formigas cortadeiras - Nascimento, Diego Arcanjo do (2018)
Teak is an exotic tree in Brazil and of great economic value to producers in the all world. Due to importance, it is necessary to invest in techniques that aim to reduce any negative effect on production, including insect attack. Mineral fertilization is an activity in the forestry sector aimed at increasing productivity, but can also act as a mechanism for plant defense. The aim of this work was to evaluate the effect of nutrient restriction on the development of seedlings and teak and later on the preference by leaf cutting ants of the species Atta sexdens and Atta laevigata. The seedlings used were of seminal origin and conducted in a greenhouse. Fertilizations consisted of mineral sources and formulated in the treatments: complete with all elements, six omissions of the nutrients -N, -P, -K, -Ca, -Mg, -Si and a control treatment. The period of 90 days was not enough to evaluate the development of seedlings. To evaluate the preference was adapted the methodology from Cherret and Seaforth (1970). There were no difference in the preference of the species of cutter ants only between treatments. The lack of mineral fertilization interfered in the development of seedlings and consequently in the preference of leaf cutting ants.